Seeking relevancy and transformation: The journey of valuing agency at a South African film school - Jenni Lynne Underhill (University of Johannesburg, 2020)
AFDA (The School for the Creative Economies) South Africa, has a consciousness â€" framed by the emerging landscape of decolonization â€" that storytelling needs to be more socially relevant than ever before. Student filmmakers find themselves at a crossroad of needing to capture characters that are relevant with a view to engendering diversity and transformation. This paper discusses the explicit need for integrating the skill of critical thinking, framed by academic argument, into the conceptual process of student film development. This is because the conceptual relevance of films has to be deepened and well expressed. In addition, the identities of characters have to be as authentic and as representative as possible. By teaching students critical thinking, and its integration into the creative process, AFDA believes that the end product will have succinct social/political meaning. AFDA has devised an innovative way to integrate student agency and research into the conceptual development stage of the student filmmaking process. This paper demonstrates how this is done and motivates how this type of approach enables promising results. Keywords: Critical thinking, Agency, Creative process, Identity, Academic argument How to cite this article: Underhill, J.L. 2020. Seeking relevancy and transformation: The journey of valuing agency at a South African film school. Scholarship of Teaching and Learning in the South. 4(2): 22-34. https://doi.org/10.36615/sotls.v4i2.117. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/